STRATEGI DIGITAL MARKETING PT HEAVENLY NUTRITION INDONESIA DALAM MEMBANGUN BRAND IMAGE PRODUK MIRUKU SEBAGAI SUSU LACTOSE FREE MELALUI MEDIA SOSIAL INSTAGRAM - Nazif Rahmawansyah; Hidayat, Aceng (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the Digital Marketing strategy implemented by PT Heavenly Nutrition Indonesia in building the brand image of Miruku as a lactose-free milk product through Instagram. This research employed a descriptive qualitative approach. Data were collected through observation, active participation during the internship program, semi-structured interviews with the Brand Manager of Miruku, and literature review. Data were analyzed using the Miles, Huberman, and Saldaña interactive model, consisting of data reduction, data display, and conclusion drawing. The findings reveal that Miruku’s Digital Marketing strategy is carried out through systematic planning and implementation stages by utilizing Instagram as the primary communication platform. The company identifies a specific target audience, develops educational content about lactose intolerance, creates lifestylerelated content relevant to the audience, and fosters engagement through Instagram features and collaborations with Key Opinion Leaders (KOLs). Instagram content plays a significant role in shaping Miruku’s brand image by strengthening brand associations through educational content, creating positive perceptions through valuable information, and reinforcing its positioning as a premium lactose-free milk product. Based on Keller’s brand image framework, the strategy contributes to the development of strength of brand association, favorability of brand association, and uniqueness of brand association. Therefore, Instagram serves as a strategic platform for establishing Miruku’s brand image as a digestive-friendly milk product that meets the needs of health-conscious and productive consumers.